Current Status and Future Directions of the National Examination Standards for Certified Sports Leader (A Comparative Study to the National Examination Standards for Licensed Nutritionists) - Deogjo Jung (Asian Society of Kinesiology, 2023)
PURPOSE The purpose of this study is to find a way to develop into the valid and reliable national examination standards that reflects field practical competency through comparative analysis with the national examination standards for licensed nutritionists, and also to find problems and future directions of the national examination standards for certified sports leader. BODY In the national examination for certified sports leader, it is important to evaluate the basic ability of physical education instructors to perform their duties in the field. In order to select sports instructors with basic job competencies required in the field, it is necessary to increase the validity of the national examination standards for sports instructors. A virtuous cycle structure must be created by appropriately measuring practical competency in the field, updating the examination criteria based on these results, and increasing the relevance and accuracy of the criteria and practical competency in the field. In addition, it is necessary to periodically re-examine and evaluate the practical competencies of the field according to the changes of the times and environment, actively change the examination criteria and reflect them in the national examination. CONCLUSIONS The validity and reliability of the national examination standards for certified sports leader must be improved in order to nurture competent exercise experts equipped with academic, professionalism, and job performance skills required in the field of physical education and sports. As a way to increase validity, problem-solving standards and item development standards should be prepared, and job performance competency evaluation should be conducted in order to nurture competent sports leaders with practical capabilities.